Batch Modification for Glass Melting Energy Reduction - Meechoowas, Ekarat; Tapasa, Kanit; Jitwatcharakomol, Tepewan (Bulletin of Applied Sciences, 2022)
Soda-lime silicate glass is produced from the commercial batch composing of sand (SiO2), soda ash (Na2CO3), dolomite (CaMg(CO3)2) and alumina (AI2O3). The batch modification is done by replacing wollastonite (CaSiO3) with magnesium oxide (MgO), and potassium feldspar (KAISi3O8) or pyrophyllite (Al2Si4O10(OH)2) with alumina. From thermodynamic calculations and Batch-Free Time testing, it was found that the modification batch had a lower melting energy (exploited heat) and higher melting ability, respectively. The modified-batch glasses also had similar chemical compositions and physical properties comparing with the original batch. This implies that the batch modification can reduce energy consumption and is probable to introduce into a large-scale glass production.